Atypical presentation of a giant lateral ventricular subependymoma, WHO grade I. Case report and literature review - Minghinelli, Federico Eduardo (Revista Argentina de Neurocirugía, 2022)
Introduction Subependymomas are rare, benign and slow-growing tumors. Its most frequent location is the fourth ventricle. They are generally less than 2 cm in size. Treatment is surgical when they generate symptoms. The objective of this work is to describe the case of an atypical presentation of a WHO grade I subependymoma and to perform a literature review. Methods A 45-year-old man consulted for headache and gait disturbance. He presented a paresis in the lower right limb. Magnetic resonance imaging (MRI) of the brain revealed a large lesion in the body of the right lateral ventricle and mild ventricular dilation. Due to these imaging characteristics that did not allow diagnostic precision and the patient’s symptoms, it was decided to remove the mass with suspected intraventricular tumor. Results Macroscopically complete excision of the lesion improved symptoms and gave a pathological diagnosis (WHO grade I subependymoma). The patient was discharged from the hospital on the 5th postoperative day. He currently has no documented complications or recurrences. Conclusion The presentation of WHO grade I subependymoma in this patient was atypical, since it was located in the right lateral ventricle and was large. Surgical excision allowed histological diagnosis and control of the disease. Key words: tumor, brain, ventricles, subependymoma, atypical